ChemInform Abstract: CaMg2P6O3N10 — A Quinary Oxonitridophosphate with an Unprecedented Tetrahedra Network Structure Type. Issue 39 (23rd September 2014) - Marchuk, Alexey; Neudert, Lukas; Oeckler, Oliver; Schnick, Wolfgang
Abstract Colorless crystals of the title compound are prepared from stoichiometric mixtures of Ca(N3)2, Mg3N2, P3N5, and PON with catalytic amounts of NH4Cl as mineralizer (Walker‐type multi‐anvil assembly, 8 GPa, 1100 °C, 1 h).